Reciclagem de pneus em fim de vida visando a fácil transferência de tecnologia - Buss, Andre Hekermann (2021)
Due to the increased production of motor vehicles, a large amount of waste is generated with different characteristics and compositions, notably from end-of-life tires, which are harmful to the environment when not disposed of properly. Its composition contains contaminating chemical elements, resulting in negative impacts to the environment. This research aims to present a process that favors the recycling of end-of-life tires, where it is easy to transfer the technology of the technique used. For the construction of the state of the art and the state of the art, a review of the rubber literature for end-of-life tires and a search on Google Patents and Espacenet using the Methodi Ordinatio was carried out. For the experimental work, samples were made using concentrations of 20%, 40% and 60% of tire rubber particles at the end of life, with the addition of thermofixed polymeric matrix of isophthalic polyester resin, catalyst, dyes and decorative material. The results of the tests indicate that the composition with 60% of usable penus rubber particles showed better results in the interpretations of the mechanical tests, than the samples containing 20% and 40%. The tests carried out in this work are those of Resistance to Deflection, Resistance to Hardness Shore D, Impact Resistance to Izod, Density by immersion, Resistance to compression, Determination of Vicat softening temperature, Scanning electron microscopy (SEM) and determination of resistance a Thermal deflection (HDT). Tests also show that waste tire particles at the end of their life promote chemical adsorption (interaction) with the thermoset polymer matrix, favoring mechanical properties. The final results of this research are: the literature review and the search for granted patents showed that this study is original; the experimental work suggests that practical applications are possible, generating a product, with a proportion of 60% particles of waste rubber tires, as indicated by the tests, with a smooth surface that does not require polishing and presents control of the generated surfaces. With this research, it is possible to verify the possibility of having a technology transfer with companies, governments and through academic means. The technology transfer was carried out with the publication of articles and the presence of this thesis. Thus, this research is characterized as innovative and also with sustainable characteristics and technology transfer presented in this thesis.